2006
DOI: 10.5194/hessd-3-499-2006
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Salt intrusion in multi-channel estuaries: a case study in the Mekong Delta, Vietnam

Abstract: Abstract. There is a well-tested theory for the computation of salt intrusion in alluvial estuaries that is fully analytical and predictable, in the sense that it has well-tested analytical equations to predict the mixing behaviour of the estuary based on measurable quantities, such as channel topography, river discharge and tidal characteristics. This theory has been described in a range of publications (Savenije, 1986, 1989, 1993) and a recent book (Savenije, 2005). This theory applies to single-channel topo… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(35 citation statements)
references
References 3 publications
0
35
0
Order By: Relevance
“…Nguyen and Savenije (2006) pointed that the high sediment transport capacity of the Mekong river and the lack of updated topographical data will affect the results of salinity models like ours. In addition, topographical changes are very difficult to predict given that future infrastructure changes are likely to influence water discharge and drainage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nguyen and Savenije (2006) pointed that the high sediment transport capacity of the Mekong river and the lack of updated topographical data will affect the results of salinity models like ours. In addition, topographical changes are very difficult to predict given that future infrastructure changes are likely to influence water discharge and drainage.…”
Section: Discussionmentioning
confidence: 99%
“…To assess sea level rise and salinity intrusion in the Mekong Delta, researchers have begun using hydrological models and GIS data since the start of this century. Specifically, the VRSAP model was used by Wassmann et al (2004) to map the vulnerable rice production areas and by Nguyen and Savenije (2006) to predict the salinity distribution in the Mekong river branches using topography, tide, and river discharge data. Hoa et al (2007Hoa et al ( , 2008 used an integrated hydraulic model, HydroGis, in tracking the impact of sea level rise and flooding in general.…”
Section: Introductionmentioning
confidence: 99%
“…The geomorphologic equilibrium form of the estuarine channel exhibits an evolution of the cross-sectional area, width, and depth toward the sea 4), 6) . It is often found that the increase in geometric parameters approximates to an exponential function of the form:…”
Section: Methodsmentioning
confidence: 99%
“…Considerable differences in the 4.0 PSU isohaline between this study and Smajgl et al [53] can be attributed to differences between the scenario setups and boundary conditions in the two studies. Nguyen and Savenije [32] tested analytical solutions of salinity simulation in the Mekong estuaries based on observed data in 2005 for the Co Chien, Cung Hau and Hau estuaries. The results showed that salinity intrusion distances from the river mouth were 41 km and 23 km for spring tide and neap tide during the dry season in 2005, respectively.…”
Section: Changes In Salinity Intrusionmentioning
confidence: 99%
“…The average discharge in the dry season fluctuates greatly, from 1700 m 3 /s to 6000 m 3 /s between January and May, and leads to water shortages for irrigating about 1.5 million hectares of irrigated crops [27]. The Mekong Delta experiences two types of tidal regime, namely the semi-diurnal and diurnal tides, affecting the hydraulic condition in estuaries of the East and West seas, respectively [32]. The salinity intrusion in the VMD-and in all the river networks-is substantial in recent years, particularly during the dry season, during which about 2.1 million hectares in the Mekong Delta suffered from salinity intrusion [21,27].…”
Section: Study Areamentioning
confidence: 99%